Principles of operating systems design & applications - Stuart, Brian L. (Course Technology, 2009)
Principles of Operating Systems: Design and Applications is an ideal resource for anyone who wants to gain a basic understanding of operating systems in the context of the applications in which they are used. The main focus of this text is to foster an understanding of operating system fundamentals: what types of services they provide, how various applications interface with them, and the restrictions they have on those applications. Making this book unique in its approach is the inclusion of a wide range of example systems and detailed case studies of the Linux and Inferno operating systems. By combining a traditional set of topics with this real-life contextual background, readers will achieve an enriched understanding of the material, which they can immediately apply to the world of operating systems.